Impact of Bacillus cereus Supplementation in Feed and Biofloc Water on Growth Performance, Immune Responses, and Intestinal Microbiota of Pacific whiteleg shrimp (Litopenaeus vannamei) - Shenwan Ding; Wenqiao Cai; Yaohai Xu; Cai Jin; Xiangrui Ma; Liang Rao; Yang Gao; Haidong Li; Zhangjie Chu (Fishes, 2026)
This study investigated the effects of dietary Bacillus cereus, administered alone or in combination with biofloc technology, on the growth performance, immune response, disease resistance, and intestinal microbiota of Litopenaeus vannamei. Shrimp fed diets supplemented with B. cereus, either directly or via biofloc systems, exhibited significantly increased final body weight and specific growth rate, together with a reduced feed conversion ratio compared with the control group. The expression levels of key hepatopancreatic immune-related genes, including lysozyme, prophenoloxidase, superoxide dismutase, Toll, immune deficiency, and Relish, were significantly upregulated in probiotic-associated treatments. Following challenge with Vibrio parahaemolyticus, cumulative mortality was markedly lower in all treatments involving B. cereus or biofloc compared with the control. Although alpha diversity indices were not significantly affected, beta diversity analysis demonstrated that supplementation frequency and delivery mode altered intestinal microbial community structure. The phyla Bacteroidota, Firmicutes, and Proteobacteria predominated across treatments, while members of Marinilabiliaceae and Shewanellaceae were enriched under probiotic-associated conditions, suggesting enhanced nutrient transformation potential. Co-occurrence network analysis further revealed increased microbial network complexity and positive interactions in probiotic and biofloc treatments, indicating improved community stability. These findings demonstrate that the synergistic application of B. cereus and biofloc technology enhances growth performance, immune capacity, and intestinal microbial resilience in intensive shrimp culture, and that supplementation strategy plays a critical role in optimizing probiotic efficacy.